Cardiac rehabilitation in older adults: Apropos yet significantly underutilized - Lutz, Andrew H.; Forman, Daniel E. (Progress in cardiovascular diseases, 2022)
Cardiac Rehabilitation (CR) is a comprehensive disease management program that utilizes exercise training, behavioral modification, education, and psychosocial counseling to optimize outcomes and functionality in patients with cardiovascular disease (CVD)1). While CR was initially designed as an exercise training and fitness program for younger patients, usually men, after debilitating hospitalizations for myocardial infarction or cardiac surgery, evidence has expanded to also include other types of CVD in women as well as men, including heart failure, valvular disease, and peripheral arterial disease2–4). As the population of older adults continues to expand, age-related CVD is endemic and is commonly associated with exercise decline, diminished quality of life, and dependence. CR has the potential to counterbalance these patterns, and therefore stands out as a particularly important consideration for older adults with CVD. Nevertheless, CR remains highly underutilized5,6). Novel approaches to CR including home-based and hybrid CR programs show promise for enhanced outreach to patients who may not otherwise participate. This review summarizes the current data available regarding CR in older adults with CVD with a focus on geriatric-specific complexities, current barriers to utilization, and approaches to enhance participation and effectiveness.